Changes in char reactivity and structure during the gasification of a Victorian brown coal: Comparison between gasification in O2 and CO2 - Tay, Hui-Ling; Li, Chun-Zhu (Elsevier, 2010)
Char reactivity is an important factor influencing the efficiency of a gasification process. As a low-rank fuel, Victorian brown coal with high gasification reactivity is especially suitable for use with gasification-based technologies. In this study, a Victorian brown coal was gasified at 800 °C in a fluidised-bed/fixed-bed reactor. Two different gasifying agents were used, which were 4000 ppm O2 balanced with argon and pure CO2. The chars produced at different gasification conversion levels were further analysed with a thermogravimetric analyser (TGA) at 400 °C in air for their reactivities. The structural features of these chars were also characterised with FT-Raman/IR spectroscopy. The contents of alkali and alkaline earth metallic species in these chars were quantified. The reactivities of the chars prepared from the gasification in pure CO2 at 800 °C were of a much higher magnitude than those obtained for the chars prepared from the gasification in 4000 ppm O2 also at 800 °C. Even though both atmospheres (i.e. 4000 ppm O2 and pure CO2) are oxidising conditions, the results indicate that the reaction mechanisms for the gasification of brown coal char at 800 °C in these two gasifying atmospheres are different. FT-Raman/IR results showed that the char structure has been changed drastically during the gasification process.